Antimicrobial and cytotoxic juglones from the immature exocarps of Juglans mandshurica. Issue 22 (17th November 2019) - Yang, Qin; Yao, Qing-Shou; Kuang, Yi; Zhang, Yue-Zhi; Feng, Ling-Ling; Zhang, Lu; Guo, Lin; Xie, Ze-Ping; Zhang, Shu-Min
Abstract: Juglonols A−C (1 −3 ), three new juglone derivatives possessing a hydroxyethyl side chain, were isolated from an organic extract of the immature exocarps of Juglans mandshurica together with five known tetralones (4 –8 ). Their structures were elucidated by extensive spectroscopic analyses and comparison with literature data. The new juglone derivatives exhibited inhibitory activities towards a panel of bacteria and fungi, as well as cancer cell lines. In contrast, the known tetralone homologues (4 −8 ) appeared to be much less efficacy. Abstract :